Kinerja Perawat dalam Meningkatkan Kepuasan Pasien di Bagian Rawat Inap Rumah Sakit Seto Hasbadi (Journal of Hospital Management, 2020)
One of the problems that are often encountered in the implementation of inpatient services in hospitals is the decrease in patient satisfaction with health services obtained in the inpatient care unit, this is usually caused by the good or bad quality of services provided by nurses to patients in hospitals that indirectly can interfere with the level of patient satisfaction with the service. The aim of this research is to analyze the competence and performance of nurses on the satisfaction of patients in the inpatient department of Seto Hasbadi Hospital. This type of research is quantitative research, with descriptive analytic using a cross-sectional study approach. The sample in this study were 68 patients who were hospitalized at Seto Hasbadi Hospital. Competency and performance variables as independent variables, patient satisfaction as the dependent variable. The research instrument used a questionnaire using the Likert scale 1-4. This study uses multiple linear regression analysis. The results of the research obtained are work competency and nurse performance simultaneously have a positive effect on patient satisfaction. Nurse work competence influences patient satisfaction. And nurse's performance influences the satisfaction of patients in the inpatient department of Seto Hasbadi Hospital. It is necessary to evaluate and evaluate nurses' competencies and performance towards patient satisfaction at Seto Hasbadi Hospital. So that from time to time it becomes a reference that can better direct the employees in increasing patient satisfaction. The research findings on work competency variables found that nurses in Seto Hasbadi Hospital were able to understand the problems patients faced, performance variables found that nurses were always in their place, and patient satisfaction variables were obtained in the clarity of financial details before entering the treatment room. The implications of this study are one of the factors that causes moderate patient satisfaction is the nurse's work competencies such as attitude and knowledge. It is necessary to evaluate and evaluate nurses' competencies and performance towards patient satisfaction at Seto Hasbadi Hospital. So that from time to time it becomes a reference that can better direct the employees in increasing patient satisfaction.Keyword: Patient satisfaction, nurse competence and nurse performance